Puzzling Hybrid, Hybrid Puzzling - Kleinsasser, Robert C (University of Muhammadiyah Prof. DR. HAMKA, 2018)
This paper further develops information from a plenary address given during the inaugural UHAMKA International Conference on English Language Teaching (ELT) and Computer assisted language learning (CALL) (UICELL 2017) in Jakarta, Indonesia, November 23, 2017. This article encourages inquiry into hybrid (blended, connected, etc.) and second language acquisition (SLA) research, teaching, and learning. Panoramic sketches survey current hybrid research and practice. Heeding Fishman and Dede’s (2016) advice, readers will be challenged to consider shifting from “educational evolution to transformation and disruption” and “investing in a robust, flexible infrastructure of people and tools” (pp. 1320-1321). Second language (L2) acquisition elements will offer potential to broaden the edges of various landscapes of L2 teaching and learning (e.g., face-to-face, online, and hybrid), while offering avenues of innovative research potential for hybrid types of investigations, in general. Readers will be enjoined to consider macro- and micro- issues where they can puzzle about the creation and development of vibrant (L2) hybrid (blended, connected, etc.) teaching, learning, and research agendas.